2014
DOI: 10.3987/com-13-s(s)83
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reactions of Azide, Furan, and Pyrrole Units with Benzynes Generated by the Hexadehydro-Diels–Alder (HDDA) Reaction

Abstract: Benzynes can be generated by the intramolecular thermal cycloisomerization of triynes–the title HDDA reaction. We report here that these can be trapped by cycloaddition reaction with trimethylsilyl azide (1,3-dipolar) or a furan or pyrrole (4+2 Diels–Alder).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Presumably (see below), the sequential cyclizations implied by the labels i, ii, and iii in substrate 13 had progressed smoothly to an anthracyne intermediate by way of the naphthyne 14 . Similarly, the anthracyne adduct 16 , a compound discussed in a later context, was formed when diethyl 3,4-furandicarboxylate 20 was used as the trapping agent. To explore whether an aromatic 2-atom linker would be compatible with a similar cascade reaction, we prepared the heptayne 17 , now containing a pair of o -substituted benzene rings rather than the two-atom ethano (or dimethylene) linkers along its backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably (see below), the sequential cyclizations implied by the labels i, ii, and iii in substrate 13 had progressed smoothly to an anthracyne intermediate by way of the naphthyne 14 . Similarly, the anthracyne adduct 16 , a compound discussed in a later context, was formed when diethyl 3,4-furandicarboxylate 20 was used as the trapping agent. To explore whether an aromatic 2-atom linker would be compatible with a similar cascade reaction, we prepared the heptayne 17 , now containing a pair of o -substituted benzene rings rather than the two-atom ethano (or dimethylene) linkers along its backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Hoye et al reported that the 1,3-dipolar (trimethylsilyl azide) and heterocyclic dienes (furan or pyrrole) could be used as an intermolecular trap for benzynes produced by the HDDA reaction of triynes to construct nitrogen-containing heterocycles with relatively high structural complexity fast. This strategy has the potential to synthesize diverse scaffolds and can be a candidate method for the discovery and synthesis of complex drugs 116 (Scheme 28g). The thermal HDDA cycloisomerization of different benzyne precursors (triyne or tetrayne) yields intermediates that can achieve different modes of intermolecular trap reactions 117 (Scheme 28h).…”
Section: Construction Of Nitrogen-containing Heterocyclic Compounds F...mentioning
confidence: 99%
“…Many useful methods are contributed to the indazole and/or dihydroindazole construction involving classical C–N bond formation. , There are also new strategies via C–C bond formation such as ortho -C–H activation of aryldiazene and Au-catalyzed three-component annulation of ortho -phenyldiyne with hydrazide, as well as the [3 + 2] cycloaddition of benzyne with hydrazine or diazomethane derivatives (Scheme ). As a new type of benzyne-involved catalyst and base-free reaction, we envisioned that the hexadehydro-Diels–Alder (HDDA) reaction could be used in the synthesis of dihydroindazole via a [3 + 2] cycloaddition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%